Modeling and control of a solar-powered cable-driven robot under power constraints - Kendouli Fairouz; Hemama Aboud; Khoudir Abed (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
This paper investigates the control performance of a solar-powered cable driven robot using MATLAB simulations, comparing a conventional proportional–integral–derivative (PID) controller with a hybrid fuzzy PD controller. The study adopts a simplified kinematic model to focus on control behavior under cable-induced nonlinearities and time-varying power availability due to solar energy, while neglecting full dynamic and cable tension effects. Both controllers were systematically tuned to ensure a fair comparison. Performance was evaluated in terms of speed and position tracking under fluctuating solar conditions. Simulation results show that the hybrid fuzzy PD controller provides superior performance, with lower RMS tracking errors, reduced overshoot, and faster settling times compared to the PID controller. These findings highlight the potential of energy-aware intelligent control strategies for improving the reliability and accuracy of solar-powered cable-driven robots operating under variable renewable energy conditions.